2017
DOI: 10.1371/journal.pone.0179717
|View full text |Cite
|
Sign up to set email alerts
|

A high-density genetic map and QTL analysis of agronomic traits in foxtail millet [Setaria italica (L.) P. Beauv.] using RAD-seq

Abstract: Foxtail millet (Setaria italica), a very important grain crop in China, has become a new model plant for cereal crops and biofuel grasses. Although its reference genome sequence was released recently, quantitative trait loci (QTLs) controlling complex agronomic traits remains limited. The development of massively parallel genotyping methods and next-generation sequencing technologies provides an excellent opportunity for developing single-nucleotide polymorphisms (SNPs) for linkage map construction and QTL ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…Therefore, a construction of a high-density linkage map could improve the accuracy of QTL mapping [27]. In recent years, with the development of sequencing technology and genome assemblies, SNP [12,26,27], SSR [16,29,30] [16] found similar results in the linkage map with 1013 SSRs markers constructed from F 2 population. However, the new map was constructed via RIL population with phenotypic stability, more markers (3413 bin markers), higher density (8.81 bin markers/Mb) and covered the whole genome.…”
Section: A Novel High-density Linkage Mapmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, a construction of a high-density linkage map could improve the accuracy of QTL mapping [27]. In recent years, with the development of sequencing technology and genome assemblies, SNP [12,26,27], SSR [16,29,30] [16] found similar results in the linkage map with 1013 SSRs markers constructed from F 2 population. However, the new map was constructed via RIL population with phenotypic stability, more markers (3413 bin markers), higher density (8.81 bin markers/Mb) and covered the whole genome.…”
Section: A Novel High-density Linkage Mapmentioning
confidence: 95%
“…A total of 69 QTLs for 21 agronomic traits were identified. Wang et al [26] mapped 11 major QTLs of eight agronomic traits using RAD-seq to detect SNP markers and screen F 2 progenies derived from the cross between Hongmiaozhangu and Changnong35. In another study, Wang et al [27] identified 57 QTLs related to 11 agronomic traits in an F 2 mapping population from a cross between Aininghuang and Jingu21.…”
mentioning
confidence: 99%
“…Since low heterozygosity values guarantee progenies with the desired genetic stability and, consequently, phenotypic uniformity [8], individuals with high homozygosity could be selected to produce precommercial varieties characterized by genetic stability and thus uniformity. The RAD-seq technique also represents an interesting tool for improving the discovery of molecular markers linked to specific traits of interest [47][48][49]. For this reason, the 4621 SNP markers were annotated through a BLASTn approach against the coding regions of Lactuca sativa, a key species in the Asteraceae family.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used 7.00 M reads per individual (Table 1 ) and utilized 587,319 (442,723 and 144,596) SNP markers for approximately 800 (400 + 400) Mb of genome sequence. The use of RAD-seq to construct linkage maps has previously required 7.28 M reads per individual (10,023 markers/1.8 Gb) in oil palm 17 , 6.70 M reads (9,968 SNP markers/423 Mb) in foxtail millet 18 , and 311.97 M reads (47,472 markers/1.1 Gb) in soybean 19 . This comparison suggests a benefit for the construction of a linkage map that has a higher precision and a lower comparative cost than RAD-seq.…”
Section: Discussionmentioning
confidence: 99%